Quantitative study on the combustion characteristics of water-in-oil emulsion droplets using high-speed imaging technique - Abdul Rasid, Ahmad Fuad; Badrul Hisham, Syazuan Hykal; Mohd Zamberi, Mahanum; Tamaldin, Noreffendy; Yang, Zhang (Penerbit Akademia Baru, 2025)
Understanding the combustion characteristics of fuel droplets is essential for optimizing combustion processes in internal combustion engines and industrial burners. Fuel droplets govern initial fuel-air mixing, vaporization, and combustion, making their study crucial. While previous research suggests that elevated water content in emulsion droplets can lead to increased burning rates, the underlying mechanism remains unclear. Potential contributors including micro-explosions, puffing, sub-droplet ejections, and surface distortions, all of which impacts the burning rates of emulsion fuel. This study aims to investigate the combustion characteristics based on the burning rate and liquid stability of water-in-diesel (WD) and ethanol-in-diesel (ED) emulsion fuels across varying temperatures. High-speed imaging and combustion analysis revealed that WD emulsions exhibit higher burning rates, with evaporation rates increased by 87.35% for WD10, 120.46% for WD20, and 130.66% for WD30 as the temperature rises from 250°C to 350°C. In contrast, ED emulsions showed smaller increases, with rates of 12.33% for ED10, 9.97% for ED20, and 10.31% for ED30 under the same conditions. WD emulsions also experienced larger droplet expansion (D² = 3.3) compared to ED emulsions (D² = 2.97) at 250°C. These findings suggest that WD emulsions, due to their volatile water content, undergo more chaotic combustion characterized by puffing and micro-explosions, while ED emulsions provide more stable combustion behaviour due to the miscibility of ethanol and diesel, which reduces the need for emulsification. This study provides critical insights into the combustion dynamics of WD and ED emulsions, highlighting their potential to improve combustion efficiency and reduce emissions. The results underscore the importance of emulsification in stabilizing combustion for WD fuels and the role of temperature and additive volume in influencing combustion behaviour. These findings contribute to the development of sustainable fuel compositions for industrial applications.